A cross sectional study to ascertain various causes of neonatal mortality using verbal autopsy in Etawah district - Ali, Nawazish; Jain, Pankaj Kumar; Shukla, Sushil Kumar; Srivastava, Dhiraj Kumar; Chaurasiya, Shailendra Kumar; Mathew, Debora Jose (International Journal Of Community Medicine And Public Health, 2020)
Background: Neonatal death is defined as no. of deaths during the first 28 completed days of life per 1000 live births in a given year or period. Around 2.6 million deaths or roughly 46% of all under five deaths had occurred during this period in 2016 which means that 7000 newborn deaths occur each day. Most of the neonatal deaths occur on the first day and week accounting to about 1 million dying on the 1st day. Objective of this study was to ascertain various causes of neonatal mortality using verbal autopsy in Etawah district. Methods: The present study was a retrospective cross-sectional study carried out for a period of 1 year (July 17 to June 2018) using WHO verbal autopsy questionnaire by finding out the study subjects from medical information system of UPUMS, Saifai and district hospital, Etawah. A total of 89 neonatal deaths were found out of which 87 were interviewed by going to their residences to get the relevant information regarding the causes of deaths. Results: Most common cause of neonatal mortality came out to be low birth weight with prematurity 44 of 87 (50.6%), followed by birth asphyxia 23 of 87 (26.4%) and sepsis 8 of 87 (9.2%). Conclusions: Effective interventions should be incorporated into policy decisions to reduce neonatal mortality due to these causes.